The Role Of Running Water Availability And Infection Prevention And Control Training In Enhancing Healthcare Workers' Practices: A Systematic Literature Review And Meta-Analysis - Iing Iing; Ade Sri Mariawati; Ayu Anulus (Jurnal Ners, 2025)
Abstract Background: Infection prevention and control training and access to running water are essential components of infection prevention. However, gaps in their implementation have been linked to suboptimal practices among healthcare workers, highlighting the need for improved training programs and infrastructure to mitigate infection risks globally. Aim: The objective of this systematic review was to assess the role of running water availability and infection prevention and control training in enhancing healthcare workers' practices. Methods: A systematic review analyzed studies (2014–2024) on running water availability and infection prevention and control training's impact on healthcare workers' practices. A random-effects model calculated adjusted odds ratios, with heterogeneity and publication bias assessed using forest and funnel plots, respectively, highlighting the importance of these factors in improving infection prevention practices. Results: We analyzed 171 abstracts, selecting 10 studies (7 on infection prevention and control training, 5 on running water) with a total of 3,818 healthcare workers. Infection prevention and control training improved good practices (AOR = 2.26; 95%CI = 2.01–2.53). Access to running water also enhanced practices (AOR = 1.96; 95%CI = 1.53–2.50). Publication bias was not significant. Discussion: Infection prevention and control training and running water access significantly improve healthcare workers’ practices. Healthcare facilities should implement mandatory infection prevention and control training and ensure access to running water to enhance infection prevention practices, particularly in resource-limited settings. Further research is needed to address publication bias and assess long-term outcomes.